Voices of the Poor : From Many Lands - Narayan, Deepa (Washington, DC: World Bank and Oxford University Press, 2013)
This is the final book in a three-part series entitled, "Voices of the Poor." The series is based on an unprecedented effort to gather the views, experiences, and aspirations of more than 60,000 poor men and women from sixty countries. The work was undertaken for the "World Development Report 2000/2001: Attacking Poverty." This publication is organized as follows: Each country chapter opens up with a brief life story. These life stories were chosen because they highlight concerns raised not only by poor women and men living in that particular community, but because the same concerns were echoed in other parts of the country. The chapters then unfold around particular sets of issues that emerged repeatedly in group discussions and individual interviews. While the findings reported in the chapters cannot be generalized to represent poverty conditions for an entire nation, the chapters bring to life what it means to be poor in various communities, in fourteen countries, from the perspective of poor people. In the final chapter, four major patterns emerge: Poor people need a diverse set of assets and capabilities if they are to survive and overcome poverty. Economy-wide policies and shocks deplete poor people's assets and increase their insecurity. The culture of mediating institutions often negatively distorts the impact of well-intended policies and excludes the poor from gains. Gender inequity within households is persistent and children are acutely vulnerable.